Bioactive compounds in human milk and intestinal health and maturity in preterm newborn: an overview - Garcia, C.; Duan, R. D.; Brévaut-Malaty, V.; Gire, C.; Millet, V.; Simeoni, U.; Bernard, M.; Armand, M. (Cellular and Molecular Biology, 2013)
Premature births are increasing worldwide (about 15 millions per year) due to several reasons (an advanced maternal age, fertility treatments, stress, smoking, nutritional deficiencies) and lead to a high societal overall cost. Among neonatal care procedures, the clinical nutrition practices are essential to promote the development and to minimize the sequelae. Premature newborns are at major risk of death by infections due to the immaturity of their intestine. Human milk provides not only nutrients but also a plethora of biologically active components that are tailored to contribute to the development of the intestinal tract early in postnatal life. Among them, some bioactive molecules exhibit trophic effects (LC-PUFA, sphingomyelin, IGF-I and IGF-II, EGF, insulin, leptin, adiponectin, lactoferrin, lactadherin, probiotics, prebiotics, miRNA) or are part of the intestinal cell membranes (PUFA, LC-PUFA, phospholipids, sphingolipids, cholesterol), others educate the intestine for innate microbial recognition (sCD14, sTLR-2, miRNA), many of them display direct fighting against pathogens (some fatty acids and monoglycerides, some phospholipids and sphingolipids, BSSL, insulin, lactoferrin, sIgAs, MUC-1, lactadherin, probiotics, prebiotics), or contribute to establish the gut microbiota (LC-PUFA, lactoferrin, probiotics, prebiotics). A synergetic action exists between several bioactive molecules. All together these precious agents regulate the maturation of the intestinal mucosal barrier, and might program early in postnatal life the future adult intestinal health. This review lists the main bioactive compounds and addresses their plausible roles and mechanisms of action.